Clinical study on acupuncture treatment of COVID-19: A protocol for a systematic review and meta-analysis. Issue 2 (14th January 2022) - Luo, Wenjun; Zhai, Yan; Sun, Mi; Guo, Dong; Xie, Fang; Yu, Zhou; Tang, Zunhao
Abstract: Background: COVID-19 is an acute respiratory infectious disease, which makes people difficult to breathe; in addition, it is often accompanied by headache, olfaction, and taste disorders of the neurological manifestations. Acupuncture has been proved to have a therapeutic effect on various neurologic manifestations. This study is designed to evaluate the effectiveness and safety of acupuncture for the neurologic manifestations in COVID-19. Methods: Randomized controlled trials from December 2019 to July 2021 will be included without restrictions on language or publication date. PubMed, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Databases (CBM), China National Knowledge Infrastructure (CNKI), Wanfang database, and VIP database will be searched. Two researchers will independently select studies, extract data, and evaluate study quality. Cochrane risk of bias tool for randomized trials will be used to assess the risk of bias of included studies. Statistical analyses will be performed using the Review Manager V.5.3 and stata 14.0. Ethics and dissemination: This study will not involve personal information. Ethical approval will not be required. We will publish the results in a peer-reviewed journal. PROSPERO Trial registration number: CRD42021265699